please solve this no spam
Attachments:
![](https://hi-static.z-dn.net/files/d84/4fb8e81ac683742dafc77da3204000f5.jpg)
Answers
Answered by
1
Step By Step Explained
/ this sing means upon
Answer:
Solution
a/b+b/a=1
a²+b²/ab=1
a²+b²-ab=0
Now, a³+b³=(a+b)(a²+b²−ab)
a³+b³=(a+b)×0=0 Ans
I Hope MY ANS IS HELPING FULL FOR YOU.
GET ANS FROM =DIVYA ARORA GARH
Similar questions
Social Sciences,
2 months ago
Science,
2 months ago
Computer Science,
2 months ago
Computer Science,
4 months ago
Biology,
4 months ago
Math,
11 months ago
English,
11 months ago